Relationship of hand anthropometry and hand grip strength in junior basketball boys - Chahal, A.; Kumar, B. (International Journal of Health Sciences & Research, 2014)
The present study was planned to collect basic data of hand anthropometry and grip strength as well as find out the association of isometric hand grip strength and various hand anthropometry in junior district level basketball players. The study was conducted on 37 district junior male basketball players of Allahabad collected from Amitabh Bachhan sports complex (Mayo-hall) Allahabad with age ranging from 10-16 years.In this cross-sectional study, the subjects were selected randomly and anthropometric measurements; viz. age, height, weight, hand width, hand length and hand span were measured for each subject by standard tools and techniques. All variables except height and weight were measured on both the sides of the body. The grip strength of both right and left hands was measured using a Jamar Grip Dynamometer at standing position with shoulder adducted and neutrally rotated and elbow straight. Result showed that hand width and hand span were greater in left hand except the hand length but it was not significant. A remarkable observation has been found out that isometric grip strength of the left / non dominant hand was higher than right/ dominant hand. May be because of hand width and hand span values were higher in left/ non dominant hand so that greater grip strength was found in the same hand than the right/ dominant hand. It may be attributed that during training as well as game both hands are widely and majorly used by the all position and in maximum techniques and tactics like left and right hand rebounding, lay ups, deflection, passing as well as fake and feints.